2018
DOI: 10.1016/j.jhep.2018.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Multi-organ assessment of compensated cirrhosis patients using quantitative magnetic resonance imaging

Abstract: Assessment of MRI parameters in a single scan session. Higher liver T 1 and reduced liver perfusion with increasing disease severity and clinical outcomes. Reduced renal cortex T 1 linked to disease severity and clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 45 publications
4
56
0
Order By: Relevance
“…Finally, liver perfusion and T 1 relaxation times of the liver and renal cortex assessed by multiparametric MRI were found to be predictive of hepatic decompensation in a cohort of 60 patients with compensated cirrhosis. 70 In conclusion, studies investigating the relationship between MR-based techniques and HVPG showed inconsistent results. Despite considerable uncertainty due to lack of standardized protocols, small sample size, and heterogenous patient populations, MR-based flow measurements (i.e., azygos blood flow and portal/hepatic artery fraction) show promise for subclassifying patients with CSPH, and possibly, even for monitoring the hemodynamic response to treatment.…”
Section: Magnetic Resonancementioning
confidence: 95%
“…Finally, liver perfusion and T 1 relaxation times of the liver and renal cortex assessed by multiparametric MRI were found to be predictive of hepatic decompensation in a cohort of 60 patients with compensated cirrhosis. 70 In conclusion, studies investigating the relationship between MR-based techniques and HVPG showed inconsistent results. Despite considerable uncertainty due to lack of standardized protocols, small sample size, and heterogenous patient populations, MR-based flow measurements (i.e., azygos blood flow and portal/hepatic artery fraction) show promise for subclassifying patients with CSPH, and possibly, even for monitoring the hemodynamic response to treatment.…”
Section: Magnetic Resonancementioning
confidence: 95%
“…MRI exploits the magnetic properties of hydrogen nuclei protons within a determined magnetic field. MRI-T1 mapping has shown promise as an effective non-invasive biomarker of fibroinflammatory disease in the liver [ 10 12 ], and also in other organs [ 12 14 ], as T1 relaxation time lengthens with increases in extracellular fluid (which may be caused by fibrosis and/or inflammation, as well as by elevated fat [ 11 ], often a precursor to pronounced hepatocyte injury [ 15 ]).The presence of iron however, which can be accurately measured from MRI-T2star (T2*), shortens the T1 [ 16 ], and thus must be accounted for. An algorithm has been created that allows for the bias introduced by elevated iron to be removed from the T1 measurements, yielding the iron corrected T1 [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, the data presented by Bradley et al 5 in this issue of the Journal herald the arrival of multi-organ quantitative MRI as an exciting and useful tool for the assessment of liver disease. Applications go beyond assessment and prognostication and include new insights into pathophysiology and a much-needed tool to better guide therapeutic intervention in portal hypertension and haemodynamically driven LROs.…”
mentioning
confidence: 86%
“…The implications of this are twofold: firstly that effective non-invasive assessment and prognostication of liver disease calls for methods that evaluate both haemodynamic and tissue characterisation; secondly, that methods focussing purely on assessing the liver are missing out on major pieces of the puzzle. 4 In this issue of the Journal, Bradley et al 5 take on this challenge by proposing a quantitative MRI protocol that measures organ volume, afferent vessel flow, tissue T1 and arterial spin labelling (ASL) perfusion in the liver, spleen and kidneys, with imaging of the heart for measurements of cardiac output and ventricular muscle mass. The MR methods proposed do not require any intravenous contrast and can be completed within a single scan lasting less than one hour, improving patient acceptability, comfort and clinical practicality.…”
mentioning
confidence: 99%